Modeling Chronic Toxicity: A Comparison of Experimental Variability With (Q)SAR/Read-Across Predictions - Helma, Christoph; Vorgrimmler, David; Gebele, Denis; Gütlein, Martin; Engeli, Barbara; Zarn, Jürg; Schilter, Benoit; Lo Piparo, Elena (Frontiers in Pharmacology, 2018)
This study compares the accuracy of (Q)SAR/read-across predictions with the experimental variability of chronic LOAEL values from *in vivo* experiments. We could demonstrate that predictions of the `lazar` algrorithm within the applicability domain of the training data have the same variability as the experimental training data. Predictions with a lower similarity threshold (i.e. a larger distance from the applicability domain) are also significantly better than random guessing, but the errors to be expected are higher and a manual inspection of prediction results is highly recommended.